Interculturality and didactics of culture in undergraduate degree French programmes in two Malaysian universities - Chin, Sin Zi (2014)
Many researchers refer to ‘intercultural’ as a macro phenomenon with a rather static approach to culture and neglect the importance of individual experience or subjectivity. As foreign language learners or instructors, one should not focus on solid culture, but regard liquid interculturality as the way for an individual to enter into a successful interpersonal communication with a speaker of another language. The standpoint of foreign language instructors on interculturality is very significant because they are the mediators between two languages (source and target languages) and the relationship between language instructors, learners and knowledge are interrelated. Therefore, the instructors’ representations play a very important role in moving from a solid intercultural approach to that of liquid interculturality. In this research I examine the representations of interculturality among native and non-native language lecturers. Semi-structured interviews were conducted with 12 lecturers teaching foreign languages in two local Malaysian universities. Participants were asked to define the interculturality and intercultural skills and how they plan to develop them among learners. The data show that there are no significant differences between the representations of interculturality between native and non-native language lecturers: they share the idea that a minimum knowledge is needed in order to communicate with native speakers. More differences can be noted in their definition of the concepts and on the way in which they attain their understanding of ‘interculturality’.